Comparing Afterlife Beliefs in Buddhism and Islam via Muslim Converts' Views - Siti Aishah, Chu Abdullah; Salinayanti, Salim; Mohd Nizam, Sahad; Suhaila, Abdullah (International Journal of Religion, 2024)
This study examines and compares afterlife beliefs in Buddhism and Islam by interviewing Muslim converts who were previously Buddhists. Using a qualitative approach, it aims to foster understanding and respect for diversity in Malaysian society. The study identifies two types of differences: shared differences in funeral rituals and distinct differences in afterlife concepts. The shared differences involve funeral traditions, while similarities in ethical principles are noted. The findings suggest that exploring afterlife beliefs through the experiences of converts provides valuable insights into the interplay of religious ideologies. Sociologically, these differences illustrate how religious doctrines influence cultural practices and social structures. Both religious incorporate cultural elements into their beliefs, promoting social cohesion and ethical conduct, shaping individual behaviours, and reinforcing family and communal bonds, thus contributing to social harmony.